2019
DOI: 10.1161/circoutcomes.118.004979
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Socioeconomic Status on Clinical Outcomes in Patients With ST-Segment–Elevation Myocardial Infarction

Abstract: Background: Low socioeconomic status (SES) has been previously shown to be associated with worse cardiovascular outcomes. However, unlike in Australia, many of these studies have been performed in countries without universal healthcare where SES may be expected to have a greater impact on care and outcomes. We sought to determine whether there is an association between SES and baseline characteristics, clinical outcomes and use of secondary prevention therapy in patients with ST-segment–elevation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 29 publications
6
40
1
1
Order By: Relevance
“…We noted greater use of PAC in admissions with higher socioeconomic status and bearing insurance coverage, which may allude to social disparities noted in other AMI populations. 47,48 Furthermore, the use of PAC in large urban hospitals and in patients with MCS demonstrates the paradigm shift in the management of AMI-CS with the advent of newer percutaneous MCS devices. 15,43,49,50 Second, with advanced MCS being available in the contemporary era, 6,7,28,29,[51][52][53] PAC is being increasingly used to treat patients with higher severity of illness.…”
Section: Discussionmentioning
confidence: 99%
“…We noted greater use of PAC in admissions with higher socioeconomic status and bearing insurance coverage, which may allude to social disparities noted in other AMI populations. 47,48 Furthermore, the use of PAC in large urban hospitals and in patients with MCS demonstrates the paradigm shift in the management of AMI-CS with the advent of newer percutaneous MCS devices. 15,43,49,50 Second, with advanced MCS being available in the contemporary era, 6,7,28,29,[51][52][53] PAC is being increasingly used to treat patients with higher severity of illness.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Australian study found similar results in patients with acute myocardial infarction (AMI). Here, lower educational level was associated with higher co-morbidity and ongoing smoking but not with risk of cardiac events after 12 months [23]. Furthermore, a Danish study found employment status and income but not educational level to be associated with an increased risk of cardiac events in patients undergoing percutaneous coronary intervention [24].…”
Section: Discussionmentioning
confidence: 99%
“…The same study in Indonesia also explained that the collectivist culture in Indonesia provides an advantage for women as they can easily get support from their core family, relatives, or friends [16]. Financial support through health insurance is essential for the sustainability of the health-care process even though low socioeconomic status is not associated with adverse clinical outcomes [24]. In a qualitative study in Denmark, patients in various socioeconomic subgroups felt excluded from cardiac rehabilitation for various reasons [25].…”
Section: Discussionmentioning
confidence: 99%